Lexical structure in lexical grammar - Karwan Omar Qadir (The Scientific Journal of Cihan University– Sulaimaniya, 2019)
The current research “Network of Words in Word Grammar” intents to interpret and analyze the opinion that Kurdish language like any language has a blending structure of nodes and Links, which make it network component. The main unit of this network is a Word, which organizes the connection between speech and comprehension in language. According to this view, the words are a node that connect all the parts and pieces of the language and make it like a network. For the achievement and investigation of these goals, the research followed the theory of (Word Grammar) in the framework of the school of (Cognitive Linguistics). The research tries to analyses theoretically and practically the node and links of network words in Kurdish language. The research is divided into four sections: The first section is entitled “Kurdish Language as Network of concepts”, ventures to represent and evaluate the network hypotheses theoretically and practically especially in Kurdish language. The second section entitled “Word Grammar Perception to Modularity of Concept”, attempts to practically illustrate the perspective of modularity of network of concept in Kurdish language. The third section entitled “Default Inheritance in Kurdish Grammar Network”, attempt to analyses the hypotheses of “Default Inheritance” theoretically, then the research practically try to reanalyze and represent this hypotheses in configuration of Kurdish grammar network. The fourth and last section entitled “Cognition of Morphology Network in Kurdish Language”, endeavors to confirm the network hypotheses in morphology of Kurdish Grammar.